2010
DOI: 10.1002/adem.201000048
|View full text |Cite
|
Sign up to set email alerts
|

Size Independent Shape Memory Behavior of Nickel–Titanium

Abstract: Shape memory alloys represent a class of so-called ''smart'' materials that can be returned to their original shape after deformation, either spontaneously or through the application of heat. While several alloys are capable of shape memory behavior, nickel-titanium (NiTi) is the most extensively researched due primarily to its relatively large deformation recoverability, [1] as well as its high strength, [2] corrosion resistance, [3] biocompatibility, [4] and high intrinsic damping. [5] The shape memory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 36 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Among these, SMAs have strong advantage in micro/nanoscale actuation, as they can generate a large force within small volume . Furthermore, the unique shape memory behavior is even preserved in the submicrometer range . For these reasons, numerous studies have been performed to determine how to apply shape memory effects (SME) to microscale actuation.…”
Section: Comparison Of Muscle Fiber and Sma Microactuatormentioning
confidence: 99%
“…Among these, SMAs have strong advantage in micro/nanoscale actuation, as they can generate a large force within small volume . Furthermore, the unique shape memory behavior is even preserved in the submicrometer range . For these reasons, numerous studies have been performed to determine how to apply shape memory effects (SME) to microscale actuation.…”
Section: Comparison Of Muscle Fiber and Sma Microactuatormentioning
confidence: 99%
“…While so far most groups have focused on studying size effects in monolith systems such as single crystals, several researchers have looked at more complex microstructures, such as nano-crystalline [43], nano-twinned [44,45], nanolaminate [46,47], and alloyed materials [48,49], to name a few. For example, Jang et al found a "smaller is weaker" phenomenon in nanocrystalline Ni-W pillars with an average grain size of 60 nm [50], while Mara et al found that the presence of closely spaced Cu-Nb nano-laminates overrides the size effect, with the strength being a function of the laminate spacing rather than the sample dimensions [46].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 5 years, a multitude of room‐temperature uniaxial compression and tension experiments have been performed on a wide range of single‐crystalline metallic nano‐pillars and nano‐dogbones, including fcc metals (Ni and Ni‐based superalloys, Au, Cu, and Al), bcc metals (W, Nb, Ta, and Mo), hcp metals (Mg and Ti), tetragonal low‐temperature metals (In), Gum metal, nanocrystalline metals (Ni), shape memory alloys (NiTi and Cu‐Al‐Ni), and a variety of metallic glasses. For samples with nonzero initial dislocation densities (i.e., excluding whiskers and nano‐fibers), a strong size effect on the flow strength was ubiquitously demonstrated as the sample size approached μm and sub‐μm dimensions .…”
Section: Optimal Design Of Micro‐architected Cellular Materialsmentioning
confidence: 99%